Identification of cost-effective biosecurity measures to reduce Salmonella along the pork production chain - Bester, Clara; Käsbohrer, Annemarie; Wilkins, Neil; Correia Carreira, Guido; Marschik, Tatiana (Frontiers in Veterinary Science, 2024)
The continued occurrence of salmonellosis cases in Europe attributed to the consumption of pork products highlights the importance of identifying cost-effective interventions. Certain biosecurity measures (BSMs) may be effective in reducing the prevalence of specific pathogens along the pork production chain and their presence in food products. The objective of this study was to identify pathogen-specific, cost-effective BSMs to reduce Salmonella at different stages of the pork production chain in two European countries - Austria (AT) and the United Kingdom (UK). For this purpose, a cost-benefit analysis was conducted based on the epidemiological output of an established quantitative microbiological risk assessment that simulated the implementation effect of the BSMs based on their risk ratios. For each of the BSMs, the associated costs and benefits were assessed individually and country-specifically. For both AT and UK, nine different BSMs were evaluated assuming a countrywide implementation rate of 100%. The results showed that four BSMs were cost-effective (benefit-cost ratio > 1) for AT and five for the UK. The uncertainty regarding the cost-effectiveness of the BSMs resulted from the variability of individual risk ratios, and the variability of benefits associated with the implementation of the BSMs. The low number of cost-effective BSMs highlights the need for holistic risk-based models and economic assessments. To increase the willingness to implement BSMs and maximize the benefits for stakeholders, who carry the majority of the implementation costs, epidemiological assessments of BSM effectiveness should consider the impact on several relevant pathogens simultaneously.